Mapping the evolution of botanical interventions for diabetic neuropathy: a two-database bibliometric landscape from 2005 to mid-2025 - Cui, Xuankai; Liu, Yilin; Guo, Zhipeng; Yang, Shuhan; Wang, Jingni; Liu, Yisong; Wang, Xingchun; Wang, Xinrui; Wang, Xingxia (Frontiers in Nutrition, 2026)
ObjectiveThis study conducts a comprehensive bibliometric analysis to map the evolutionary trajectory, identify research hotspots, and forecast future trends in botanical interventions for diabetic neuropathy (DN) from 2005 to mid-2025.MethodsWe retrieved relevant publications from the Web of Science Core Collection and PubMed (2005 to mid-2025). After applying inclusion criteria and removing duplicates, 414 articles and reviews were analyzed using VOSviewer, CiteSpace and Bibliometrix to visualize publication trends, collaboration networks, and keyword dynamics.ResultsAnnual publication output exhibited exponential growth after 2020, peaking at 71 publications in 2024. China dominated the research output, followed by India and the USA, though international collaboration remained limited. Keyword analysis identified four major research hotpots: molecular mechanisms (e.g., oxidative stress, NF-κB), clinical translation, systems pharmacology of traditional Chinese medicine (TCM), and signaling pathways. Burst detection revealed “network pharmacology” and “TCM” as the current research frontiers.ConclusionResearch on botanical interventions for DN is rapidly expanding, with a clear shift toward mechanistic and computational approaches. Future efforts should prioritize robust clinical trials, international cooperation, and deeper mechanistic studies to translate botanical potential into evidence-based therapies.